A gestão do currículo escolar da rede municipal de ensino de Goiânia: entre "obrigações" curriculares e práticas "autônomas" - Reis, Geovana (2015)
This work is linked to the State Research Line, Politics and History Education program of the Universidade Federal de Goiás Post-graduate School o f Education. The purpose of this research is to analyze and understand how the curriculum management by teachers of the Goiânia Municipal Education System (RME) is performed. The study starts from the concept of curriculum discussion, trying to observe its historical development, complexity and contained polysemy, approach the curriculum management from mediations suffered by theories and policies. They can be prepared in different spaces / instances, by different agents, be embodied in official documents, standards or laws, books and also in teaching practice. Thus, the curriculum management is understood in this paper as conformation given by teachers to what and how to teach, considering the curricular sources variety for the concrete reality of their classrooms. It is important to emphasize that both theories as the curriculum policies, contain elements that can interfere in curriculum management performed by teachers and therefore, this thesis sought working these three concepts: Curriculum theory, curriculum policies and curriculum management. It was found that, despite regulations that curriculum policy may provide the curriculum management, this, has taken place autonomously and for its achievement, teachers have used a variety of research sources, since those from the oficial curriculum policies (national and local) to the unofficial (textbooks and books, web sites, etc.), adapting them to the reality of their classrooms, and eventually resorting to curricular theories according to their immediate needs. Therefore, the curriculum management undertaken by the Goiania RME teachers seems to be the result of the official curriculum interference, proposals or curriculum guidelines, educational materials and many other sources, all mediated by the pedagogical habitus of each teacher.